Upaya Meningkatkan Motivasi Belajar Materi Sistem Klasifikasi Makhluk Hidup dengan Model Pembelajaran Kooperatif Jigsaw - Ernie Setyawati (Journal on Education, 2023)
Pontianak 3 Public Middle School, especially in class VIIF, there are indications that students are less interested in science subjects. This is based on the results of the questionnaire that the researcher distributed in this class, before the class action was carried out. 70% of students in class VIII F consider science as a difficult subject, with lots of foreign and uninteresting terms. That's why researchers try to apply variations of the TIP (Know-Want-Learn) Jigsaw Assisted Graphic Cooperative Learning model to overcome this. This learning model is quite interesting, because it is assisted by the TIP Graphic Manager which is accompanied by colorful pictures and worksheets which can bring up students' ideas in the learning process. The results of observations during the study showed that students began to appear enthusiastic when the jigsaw type cooperative learning model assisted by the TIP graphic controller was applied in class VII F. Students were asked to communicate the results of their understanding during the learning process. When studying in groups all students can complete assignments on time. And the result, 92% of students from 33 students can achieve the KKM score. While the results of the pretest, there were 29 students who were able to achieve the KKM or 81%. There was an increase of 13%. Based on this research, the researchers suggest that science teachers at SMPN 3 Pontianak try to apply a jigsaw type cooperative learning model assisted by a TIP graphical controller when learning with material on classification systems in living things. The creativity of extraordinary students will be seen when they present their skills. Besides being able to increase learning motivation, this method can also be used for habituation which can foster creativity besides that this method is also to train students to be confident in communicating so that students can express their ideas when the learning process takes place.